PROBLEMS AND SPECIFIC CHARACTERISTICS OF TEACHING SPEECH GRAMMAR IN A FOREIGN LANGUAGE (TAMADDUN NURI JURNALI, 2025)
Teaching speech grammar in the process of communication forms the ability of students to correctly understand grammatical rules and apply them in communication. However, this process faces many difficulties, including grammatical interference, the gap between theory and practice, lack of motivation of students, and inflexibility of textbooks. The article discusses ways to overcome these problems, including the use of a communicative approach, interactive methods, and flexible teaching aids.